The Role of Social Media in Shaping Political Discourse and Public Opinion in the Digital Age - Syabania Hasana Muhammad (Mahogany Journal De Social, 2024)
media in the digital age influences political conversations, attitude construction, polarization, and political activism in the political society.  Nevertheless, to assess the effects of social media on the political process and information flow, the qualitative research methodology was adopted in this study, and this required interviewing the respondents and studying the contents of their posts.  The information indicates that social media drives individuals to extremism and hate and dictates political language.  The findings of the research indicate that fake news and bais have a role in the formation of opinion among the consumers, where a significant number of users could not tell the difference between fake and real news.  Findings of this paper further reveal that social media constitutes an important source of both digital activism, culminating to slacktivism, also known as low-effort activism, and political events where they happen.  In this regard, the research addresses the gaps in the literature by presenting a more complex and elaborate view of the opportunities and challenges that social media may present to the political world. It also demonstrates how social media can be used to polarize and empower the political participation of people.  The conclusion of the paper will provide thoughts and suggestions on possible future studies of the potential of social media to foster polite dialogue and social depolarization.